Self-Efficacy Guru Gen-Z dalam Menggunakan Artificial Intelligence (AI) untuk Mendukung Pembelajaran Matematika - Vina Mahmudah Julianti; Diar Veni Rahayu; Redi Hermanto (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
This study aims to describe the self-efficacy of Generation Z mathematics teachers in using Artificial Intelligence (AI) to support mathematics learning. This topic is important because Gen-Z teachers are beginning to dominate the new teaching staff and are participating in driving technology-based learning innovation. However, familiarity with technology does not always indicate self-confidence in integrating AI pedagogically, especially in mathematics learning that requires conceptual understanding and adaptive learning strategies. This study used a quantitative descriptive method by selecting 17 mathematics teachers from 14 schools. Data were collected using a valid and reliable questionnaire based on Bandura's self-efficacy dimensions, namely level/magnitude, strength, and generality. The results showed that the level of teacher self-efficacy was generally in the high category, with the strength dimension being the most dominant. Most teachers had strong confidence in using AI despite facing obstacles, while a small number were still in the moderate category. These findings indicate the need to strengthen pedagogical competence to optimize the use of AI in mathematics learning.Keyword: self-efficacy, Artificial Intelligence, mathematics teachers, Generation Z, technology integration.